Functionalized Metal‐Supported Reversible Protonic Ceramic Cells with Exceptional Performance and Durability - Yuhao Wang; Yufei Song; Jiapeng Liu; Kaichuang Yang; Xidong Lin; Zhibin Yang; Francesco Ciucci (Advanced Energy & Sustainability Research, 2022)
Reversible protonic ceramic cells (RePCCs) are limited by several factors, including high cost, poor stability, and insufficient fuel electrode activity toward fuel oxidization/generation reactions. Herein, a novel Ni−Fe metal‐supported RePCC (MS‐RePCC) to address these issues simultaneously is proposed. Specifically, the Ni−Fe support possesses good mechanical strength and thermal compatibility with cermet‐based electrodes/electrolytes, ensuring a facile cell fabrication and robust durability. Density functional theory calculations suggest that Fe in the Ni−Fe support enhances the fuel electrode functional layer by providing additional and more active sites for the electrocatalytic reactions. The as‐fabricated MS‐RePCC at 700 °C achieves an excellent peak power density (PPD) of 586 mW cm−2 and an electrolysis current of −428 mA cm−2 (at 1.3 V). Furthermore, the cell is exceptionally stable, as evidenced by 930 h of fuel cell operation with ultralow degradation (≈0.78% kh−1), and much better than an analogous anode‐supported cell (≈17.78% kh−1). In addition, the cell is stable for 50 h of reversible fuel cell/electrolyzer cycling, further demonstrating the potential of this MS‐RePCC. This article proposes a simple and new approach to enhance the electrochemical activity and durability of RePCC, thereby accelerating the commercialization of this technology.